Assessing the Educational Needs of Canadian Gastroenterologists and Gastroenterology Nurses: Challenges to Optimal Care in Crohn’s Disease - Martin Dupuis; John K Marshall; Sean M Hayes; Kayla Cytryn; Suzanne Murray (Canadian Journal of Gastroenterology)
OBJECTIVE: A national needs assessment of Canadian gastroenterologists and gastroenterology nurses was undertaken to determine the perceived and unperceived educational and performance barriers to caring for patients with Crohn’s disease (CD).